A DFT study of Ni-catalyzed (3 + 3)-annulation between donor–acceptor cyclopropanes and diaziridines. Issue 8 (9th March 2023) - Dai, Song-Shan; Yang, Xiao-jiao; Fang, Ran; Kirillov, Alexander M.; Yang, Lizi
Abstract : The mechanism and stereoselectivity of the Ni-catalyzed [3 + 3] annulation between donor–acceptor cyclopropanes (DACs) and diaziridines were rationalized by DFT calculations. Abstract : The mechanism and stereoselectivity of the Ni(ii )-catalyzed [3 + 3] annulation between donor–acceptor cyclopropanes (DACs) and diaziridines were studied by DFT calculations. The obtained results show that the entire reaction comprises three main steps: (1) nucleophilic attack of diaziridines on DACs to form a quaternary ammonium intermediate; (2) cleavage of the unstable C–N bond in the quaternary ammonium intermediate to generate the key intermediate; (3) cyclization of the key intermediate involving two carbon atoms with opposite charges to obtain products with different configurations via distinct six-membered ring transition states. Based on the calculation results, the reaction between DACs of R -configuration and diaziridines with five-membered ring substituents leads to a predominant E -configuration product. However, Z -configuration products are the major outcome of the reactions involving S -configuration DACs. When R -configuration DACs react with diaziridines containing six-membered rings, the key intermediates of Z -configuration are more stable, thus resulting in the main products with Z -configuration. Furthermore, the distortion/interaction analysis revealed that the configuration of the final product is dominated by the distortion energy and is closely related to that of the key intermediate. This theoretical study might provide new perspectives toward predicting the reaction pathways and rationalizing selectivity features in related types of annulation reactions.